Westernization and Colonization of the Mind in Chinua Achebe’s “Dead Men’s Path” - Maria Regina Anna Hadi Kusumawardani (OKARA: Jurnal Bahasa dan Sastra, 2021)
British occupation in Nigeria has brought several impacts to the native land and also the indigenous people. Westernization and colonization of the mind are two inseparable effects of colonialism. These two issues are oftentimes depicted in literary works focusing on colonialism as their theme. The aim of this study is to analyze the issues of westernization and colonization of the mind raised in Chinua Achebe's "Dead Men's Path." The data were taken from quotes that prove the existence of these issues from a short story entitled “Dead Men’s Path” by Chinua Achebe and analyzed them using Homi Bhabha’s theory of mimicry and Ngũgĩ wa Thiong’o’s theory of colonization of the mind. The results showed that westernization and colonization of the mind have affected Michael Obi, the main character in the story. Westernization influences Obi to adopt modern life and Western thoughts that show the process of mimicry, while colonization of the mind makes Obi downgrades Nigerian cultures. The issue of the management of land was also found in the story as a continuation of the previous problems. “Dead Men’s Path” by Chinua Achebe reveals that British colonialism has changed the perspectives of Nigerian elites, as seen in Michael Obi’s story.